Practices and Spaces (Location): Reflecting on the Contribution of Writing Centres for Decolonisation in Higher Education - Ntuthuko Mhlongo; Nonhlanhla Khumalo; Denver Naidoo; Nthabeleng Tamako (African Journal of Inter-Multidisciplinary Studies, 2023)
The location of writing centres in universities has attracted attention from practitioners and researchers in the field of academic support scholarship. These writing centres, known as spaces where students discuss their writing ideas, have become part of the decoloniality discourse in South African higher education. This study adopts a mixed-method approach and builds upon Grimm's theory of transitional space to examine tutor perspectives on the contribution of writing centres' pedagogical practices and physical location to the decolonisation of education at the Durban University of Technology (DUT) and Mangosuthu University of Technology (MUT). The findings reveal that the writing centres in these contexts contribute to the decolonial agenda by employing various approaches such as multilingualism and one-on-one consultations that are sensitive to the African context. However, despite these positive contributions, it is necessary to initiate decolonial discussions that address historical past injustices. The study recommends that the creation of decolonised spaces is a complex process requiring collaborative engagement between writing centres and the university community, including management. Writing centres have an integral role to play in decolonising the university space, particularly in the South African context.